(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
From combating terrorism to securing its nuclear arsenals, Pakistan has always tried to fulfill its international commitments and obligation as a prudent nuclear state. With a systematized command and control mechanism in place, Pakistan has taken multiple concrete steps to prove its obligation to global peace and security in general and disarmament, nuclear non-proliferation and strategic export controls in particular. This paper aims to highlight some of tangible actions taken by Pakistan to guarantee the safety and security of its nuclear program with particular focus on the introduction and implementation of strategic Export Control mechanism in Pakistan pursuant to UNSC resolution 1540. The purpose is to establish the fact that Pakistan’s commitment to WMD non-proliferation, disarmament is at par with international standards and requirements along with a strong safety and security mechanism of its nuclear installation. A fact needs to be acknowledged more by international non-proliferation community. Furthermore, this study underscores Pakistan’s ongoing efforts to align its nuclear security measures with evolving global norms, showcasing its proactive stance in countering emerging threats. By maintaining stringent regulatory frameworks and engaging in international cooperation, Pakistan continues to demonstrate its dedication to upholding global non-proliferation objectives. Additionally, Pakistan’s robust participation in international forums and its adherence to global treaties further cement its position as a responsible nuclear state.